2013
DOI: 10.1007/s11013-013-9336-9
|View full text |Cite
|
Sign up to set email alerts
|

“Now he walks and walks, as if he didn’t have a home where he could eat”: Food, Healing, and Hunger in Quechua Narratives of Madness

Abstract: "Now he walks and walks, as if he didn't have a home where he could eat": food, healing, and hunger in Quechua narratives of madness Article (Accepted Version) http://sro.sussex.ac.uk Orr, David (2013) Copyright and reuse:Sussex Research Online is a digital repository of the research output of the University.Copyright and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable, the material made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(14 reference statements)
0
8
0
1
Order By: Relevance
“…Subsequent research outside of Western settings, e.g., in Laos [13], Ethiopia [3, 14], Peru [15], Indonesia [16], China [17] and Uganda [18] generally confirm these findings. A systematic review of explanatory models of psychosis presents a more nuanced perspective [19].…”
Section: Introductionmentioning
confidence: 77%
“…Subsequent research outside of Western settings, e.g., in Laos [13], Ethiopia [3, 14], Peru [15], Indonesia [16], China [17] and Uganda [18] generally confirm these findings. A systematic review of explanatory models of psychosis presents a more nuanced perspective [19].…”
Section: Introductionmentioning
confidence: 77%
“…Almost all of the Bolivian migrants living in Sa˜o Paulo, Brazil, have a Quechua background. For this group, mental suffering and the presence of mental disorders are less understood as individualized pathology and more as a disturbance in family and social relationships (Orr 2013). So, we can hypothesize that understand mental illness as socially-based could on one side reduce the stigma and on the other side, make it more difficult to identify an individual in need of professional help for a mental health issue.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of food in the health-illness process is another issue that arose in this study. In Orr's [25] publication about "Food, Healing, and Hunger in Quechua Narratives of Madness," three overlapping categories emerged: food as symptoms, as an explanatory model, and as a facet of healing. In our study, we observed that nutrition is also referred to in these three ways; participants thought that poor nutrition creates illness, that a sick person cannot "eat with pleasure" and that food is also used as an important part of the healing process.…”
Section: Illness Definitionmentioning
confidence: 99%